A 100 m/320 Gbps SDM FSO link with a doublet lens scheme. (15th June 2016) - Li, Chung-Yi; Lu, Hai-Han; Lu, Ting-Chien; Wu, Chang-Jen; Chu, Chien-An; Lin, Hung-Hsien; Cheng, Ming-Te
Abstract: A 100 m/320 Gbps space-division-multiplexing (SDM) free-space optical (FSO) link with a doublet lens scheme is proposed and experimentally demonstrated. The transmission capacity of FSO links is increased significantly by the SDM topology, and the transmission distance of FSO links is greatly extended by the doublet lens scheme. An FSO link of eight channels over a 100 m free-space link with a total transmission rate of 320 Gbps (40 Gbps/ λ   ×  8 λ   =  320 Gbps) is achieved. With the assistance of a low noise amplifier (LNA) and clock/data recovery (CDR) at the receiving site, a good bit error rate (BER) performance and a clear eye diagram are obtained at 100 m/320 Gbps. The proposed 100 m/320 Gbps SDM FSO link is shown to be a notable option to provide the advantages of long transmission distances and high transmission rates for optical wireless communications.